2020
DOI: 10.1155/2020/8826238
|View full text |Cite
|
Sign up to set email alerts
|

EEG Assessment in a 2-Year-Old Child with Prolonged Disorders of Consciousness: 3 Years’ Follow-up

Abstract: A 2-year-old girl, diagnosed with traumatic brain injury and epilepsy following car trauma, was followed up for 3 years (a total of 15 recordings taken at 0, 2, 3, 4, 5, 6, 7, 9, 10, 11, 12, 14, 19, 26, and 35 months). There is still no clear guidance on the diagnosis, treatment, and prognosis of children with disorders of consciousness. At each appointment, recordings included the child’s height, weight, pediatric Glasgow Coma Scale (pGCS), Coma Recovery Scale-Revised (CRS-R), Gesell Developmental Schedule, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…(++) In children with VS/UWS, EEGs were used to confirm consciousness status when wide cortical damage presented with brain stem preservation 34 to detect residual cortical activity and connectivity, revealing potential for improvement and to study common DoC complications, such as epileptic abnormalities. 35 Stimulation paradigms combined with ERP recordings were used to assess responsiveness in children with DoC.…”
Section: Evidencementioning
confidence: 99%
“…(++) In children with VS/UWS, EEGs were used to confirm consciousness status when wide cortical damage presented with brain stem preservation 34 to detect residual cortical activity and connectivity, revealing potential for improvement and to study common DoC complications, such as epileptic abnormalities. 35 Stimulation paradigms combined with ERP recordings were used to assess responsiveness in children with DoC.…”
Section: Evidencementioning
confidence: 99%
“…This technique is widely used in adults with DOC. In one case report, Xu et al 18 used resting‐state EEG recordings to repeatedly assess a 2‐year‐old female with prolonged DOC over 3 years. They performed EEG spectral analysis and showed that the delta‐band power spectrum continuously increased over the 3 years and was associated with a poor neurodevelopmental outcome, as assessed by the Gesell test measure.…”
Section: Resultsmentioning
confidence: 99%
“…decreased parietal SWA regulation), 22 or resting‐state EEG (i.e. increase in the delta‐band power spectrum) 18 could also be useful. However, they should be used carefully in clinical settings since poor prognosis decision‐making can lead to dramatic consequences.…”
Section: Discussionmentioning
confidence: 99%
“…(Multi)sensory stimulation is at the core of early intervention. It aims to generate a comprehensive set of environmental prompts by stimulating all the five senses and the motor system [ 32 , 33 ], and it is deemed to favour the re-organisation and the re-building of the behavioural repertoire [ 34 ]. The ultimate goal is to leverage residual activation to—at least ideally—reach out to the entire brain network and foster functioning in the damaged neural tissue through facilitation [ 35 ].…”
Section: Neurorehabilitationmentioning
confidence: 99%
“…Repetitive Nerve Stimulation aims at providing electrical stimulation to a primary nerve afferent to the brainstem (and cortex) ( Figure 1 A) [ 73 , 74 ]. A preliminary report on one child [ 32 ] showed both the short- and long-term positive effects on functional brain connectivity.…”
Section: Medical Technologies For Treatmentmentioning
confidence: 99%